A Systematic Literature Review of Mobile Learning Applications in Environmental Education from 2011-2021 - Widiastuti, Nabila Lailil (Tauladan Fathimah Azzahra, 2022)
This systematic literature review aims to capture the trends in the use of mobile learning in environmental education from the Springer database. As inclusion criteria, all article journals should be written in English and published between January 2011 and September 2021. The categories to be analyzed were the distribution of annual publications, the number of publications by journal, the number of authors, research methods, the use of the terms mobile learning or environmental education in the title, and the most productive countries. A total of 378 research articles published in the last decade on mobile learning showed a gradual increase over the last ten years. The most published articles about mobile learning are in 2020. In addition, the most commonly used research method is research and development, the most frequently published articles in this field have 3 authors, the most productive journal is Education and Information Technologies, and the most productive country is the US.